Benefits of Moringa oleifera Lam. leaves as a healthy drink - Bialangi, Mursito S.; Lilies, Lilies; Mawaddah, Hayyatun; Potutu, Harmani (Univeritas Papua, 2024)
Apart from being used as a food ingredient, water purifier or cosmetic ingredient, the moringa plant can also be used as a health drink in the form of moringa tea. Other benefits of moringa leaves are as a chemopreventive, increasing the body's endurance, nutrition for the eyes and brain, eliminating signs of wrinkles on the face, and as an antioxidant. However, unfortunately not all people know about the benefits of the moringa plant as a nutritious plant. This article is a literature review to analyze the benefits of moringa leaves as a health drink. The results of the literature analysis that has been carried out show that the moringa plant contains a number of important nutrients that are needed for body health. The nutrients in moringa include vitamin C which is equivalent to seven times that of oranges, calcium equivalent to four times and protein equivalent to twice that of milk, vitamin A equivalent to four times that of carrots, and potassium equivalent to three times that of bananas. Apart from that, it also contains high levels of antioxidants, so the Moringa plant is very important for warding off free radicals. Several research results have found that moringa leaf extract can reduce blood glucose levels in white mice. People can be encouraged to use the moringa plant in their daily lives. Based on the explanation in this article, people can cultivate the use of moringa leaves as a drink to overcome health problems. Through the development of moringa plants as a typical plant and raw material for herbal tea in the Central Sulawesi area, communities can be empowered to utilize empty land to plant Moringa.